The Urgency to Prevent Illicit Political Party Fundraising Through the Anti-Money Laundering Regime in Indonesia - Nathalina Naibaho; Patricia Rinwigati; Ahmad Ghozi (Asia-Pacific Journal of Elections and Democracy, 2021)
An election is a democratic process, which is both costly and cumbersome for anyone who wishes to participate. Existing practices, precisely in Indonesia, show that both political parties as well as candidates often need to raise funds to finance their campaign and/or their programs, as well as to ensure the sustainability of their political parties. The Indonesian law states various financial resources in which a political party can raise. Nevertheless, it does not set the limitations and restrictions, particularly on ways to identify and monitor where funds come from. Hence, there has been a fear that political parties may use this loophole to conduct money laundering. It is argued that while the money laundry regime can be used to prevent conspicuous practices related to political financing, a legal framework has yet to be designed and implemented.